The future of the World Trade Organization - Biswajit Dhar (Asian Development Bank Institute (ADBI), 2013)
The continued difficulties of the World Trade Organization to achieve further multilateral trade liberalization in the Doha Round negotiations have raised questions about its continued relevance. This paper firstly identifies and assesses the key developments in the Doha Round that have contributed to the present stalemate. Secondly, it presents several options that the organization could consider for defining its future work program, given the new realities of global economic engagement, especially the emergence of global production networks. Most importantly, the paper assesses the possibility of including new disciplines covering areas that can help the growth of these drivers of global economic integration. Such an initiative could include three sets of issue: trade facilitation measures, an equitable investment regime, and effective disciplines for curbing non-tariff barriers.
Keywords: F13; F53; 330; WTO; international cooperation; trade; investment; production networks; trade facilitation; non-tariff barriers; Internationale Wirtschaftsbeziehungen; Unternehmensnetzwerk; Internationale Handelspolitik; WTO-Verhandlungen